Sound Radiation Analysis and Noise Reduction Design of Railway Wheel - ZHA Guotao; FU Rong; FU Liang; TU Fengchen; HE Caichun (机车电传动)
The wheel radiation noise is an important contributor of railway noise. Based on the acoustic simulation and experimental techniques, this paper analyzed the radiation noise characteristics of a wheel, and designed a noise reduction wheel combined with constrained damping and vibration absorbing technology. The results of the wheel acoustics test showed that the noise reduction method has a good noise reduction effect. The amplitude of the acoustic transfer function was reduced by one to two orders of magnitude, and the total sound power level was reduced by above 11 dB (A).